Indigo chromophores and pigments: Structure and dynamics. (January 2020) - Volkov, V.V.; Chelli, R.; Righini, R.; Perry, C.C.
Abstract: In this study, we explore the molecular mechanisms of the stability of indigo chromophores and pigments. Assisted with density functional theory, we compare visible, infrared and Raman spectral properties of model molecules, chromophores and pigments derived from living organisms. Using indigo carmine as a representative model system, we characterize the structure and dynamics of the chromophore in the first electronic excited state using femtosecond visible pump-infrared probe spectroscopy. Results of experiments and theoretical studies indicate that, while the trans geometry is strongly dominant in the electronic ground state, upon photoexcitation, in the Franck-Condon region, some molecules may experience isomerization and proton transfer dynamics. If this happens, however, the normal modes of the tran s geometry of the electronic excited state are reconfirmed within several hundred femtoseconds. Supported by quantum theory, first, we ascribe stabilization of the trans geometry in the Franck-Condon region to the reactive character of the potential energy surface for the indigo chromophore when under the cis geometry in the electronic excited state. Second, we suggest that a conical intersection crossing, due to the high barrier along the isomerization pathway in the ground state, would provide for the effective relaxation and observed dominance of the trans geometry of the chromophore in the ground state. Planarity of the chromophore under the trans geometry assists effective dissipation of energy via a cascade of in-plane C-C, C-O⋯H-N stretchings and C-C-C bending modes delocalized over the molecular mainframe. The described mechanisms help to explain the remarkable photo-stability of indigo chromophores. Graphical abstract: Image 1 Highlights: Electronic, infrared and Raman of indigo from natural specimens, and indigo carmine. Femto visible pump – infrared probe of structure and relaxation in the excited state. Low frequency Raman modulations on energy relaxation in the electronic excited state. Density functional theory along the photo-isomerization and proton transfer pathways. Molecular mechanisms for effective energy dissipation and indigo photo-stability.